Isten kertésze – a vallástanár személye - PÜSÖK, Sarolta (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2018)
God’s Gardener – the Character of the Religion Teacher This topic is always an actual issue, every generation has to reconsider it. The present study tries to integrate and enumerate the relevant Hungarian Reformed literature referring to the subject. The most precious tool/instrument: In the religious education the relationship between the Holy Spirit, the pupil and the teacher is very significant. The latter acts like an important tool in God’s hand, playing a key role when it comes to answering the existential questions of the pupils. Two-sided approach: The religion teacher does not simply provide information through lessons, they encourage the right perception of God and the relationship with Him, thus their personal relationship with Him should be transparent, and loving kindness should describe how they treat children. “We are visible... we are being tracked, followed.” This subtitle is a quote referring to the exemplariness of the religion teachers. In an era of paradigm crisis this problem gets even more complex, what kind of patterns and ideals does a Christian school provide? The religion teacher should act like an ideal, an example which is authentic, honest and can admit their own failures. The two secrets of a good educationist: self-understanding and self-identity. Being a good teacher requires profound self-understanding viewing their past, and conscious self-development in the future, Christian 4 dimensional growth . Conclusion. The attitude of a religion teacher influences the social status of the church and judgment of the whole Christian community through the pupils. Devoted, committed teachers can make their work fruitful if they engage lifelong learning, while they teach they constantly acquire new knowledge and skills.